Developing explosive power and increased speed-force readiness in young wrestlers - Kerimov, F. A.; Goncharova, O. V. (International Journal of Wrestling Science, 2014)
The paper discusses the current views on the methodology for development of special power-speed in the physical education of children 9-10 year old wrestlers. We used specially selected traditional speed-strength exercises used to develop "explosive" muscle power. These indicators allowed us to define options for the development of explosive strength of muscles in young wrestlers using the shock method.